FREQUENCY CHARACTERISTICS OF THE GENES OF THE SECOND PHASE OF DETOXIFICATION OF XENOBIOTICS IN WOMEN OF rUSSIAN AND BURYAT ETHNIC GROUPS - E. E. Stupko; T. B. Tsyrenov; A. V. Labygina; L. V. Suturina; L. I. Kolesnikova (Acta Biomedica Scientifica)
The article presents the results of the analysis of the distribution of genotypes and alleles of polymorphic loci gene GSTP1 (*A, *B, *C, *D), GSTT1 (del) and GSTM1 (del) in 28 women Russian and 30 women of Buryat ethnic groups. As a result, the work showed a statistically significant difference in genotype AC gene GSTP1 among the study groups. As carriers of other genotypes of genes GSTP1, GSTT1, and GSTM1 showed no significant difference